2007
DOI: 10.1038/sj.ejcn.1602725
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on dietary intakes of folate, betaine, and choline and cardiovascular disease risk in women

Abstract: Objective: To investigate the association between dietary intakes of folate, betaine and choline and the risk of cardiovascular disease (CVD). Design: Prospective cohort study. Subjects: A total of 16 165 women aged 49-70 years without prior CVD. Subjects were breast cancer screening participants in the PROSPECT-EPIC cohort, which is 1 of the 2 Dutch contributions to the European Prospective Investigation into Cancer and Nutrition (EPIC). Methods: Each participant completed a validated food frequency questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 46 publications
8
87
0
1
Order By: Relevance
“…However, our data were consistent with recent prospective studies from both a Norwegian sample of patients with suspected stable angina pectoris (30) and an American generalpopulation sample (31) that showed an inverse relation between plasma betaine and the presence of type 2 diabetes. In addition, analyses of 4 other cohorts showed no relation between dietary intake of betaine or choline and the incidence of peripheral artery disease (32), incidence of coronary heart disease (33), or cardiovascular disease risk (34). However, an analysis of a large prospective cohort with stable angina pectoris showed increased risk of acute myocardial infarction in individuals with plasma choline concentrations in the highest quartile than in the lowest quartile (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, our data were consistent with recent prospective studies from both a Norwegian sample of patients with suspected stable angina pectoris (30) and an American generalpopulation sample (31) that showed an inverse relation between plasma betaine and the presence of type 2 diabetes. In addition, analyses of 4 other cohorts showed no relation between dietary intake of betaine or choline and the incidence of peripheral artery disease (32), incidence of coronary heart disease (33), or cardiovascular disease risk (34). However, an analysis of a large prospective cohort with stable angina pectoris showed increased risk of acute myocardial infarction in individuals with plasma choline concentrations in the highest quartile than in the lowest quartile (26).…”
Section: Discussionmentioning
confidence: 99%
“…High intake of choline and betaine was associated with diminished inflammation in one study (66,67). However, an alternative report noted only a modest association with choline and betaine intake and CVD (68), which lost significance following adjustments for CVD risk markers (67,69). Nevertheless, any nutritional study has a confounding factor of evaluating a broad mix of nutritional factors that may have opposing effects.…”
Section: R E V I E W S E R I E S : G U T M I C R O B I O M Ementioning
confidence: 99%
“…However, two large prospective studies conducted in 2007 based on the subjects in the Dutch PROSPECT-EPIC cohort [70] and the Atherosclerosis Risk in Communities (ARIC) study [71] demonstrated no association between choline and betaine consumption and CVD. It has been noted, however, that these null findings may be due to the large measurement error of intake estimates for choline and betaine [72].…”
Section: Human Studiesmentioning
confidence: 99%
“…In addition, the mechanisms outlined to explain this association are also based on pathophysiological conditions such as enhanced PLD activity and mitochondrial dysfunction. Infact, regular dietary intakes of choline and betaine was not associated with an increased risk of CVD in a large-scale prospective cohort study of over 16 000 healthy women [78].…”
Section: Human Studiesmentioning
confidence: 99%